Advantages of cyclic rectification for ethanol production - Bulii, Yurii; Forsyuk, Andriy; Bondar, Nikolai; Оbodovych, Оlexandr (My University, 2024)
The energy dependency of industrialized nations requires for alternative sources of energy, one of which is ethyl alcohol (bioethanol). To ensure the competitiveness of bioethanol over carbohydrate energy sources, the development and implementation of innovative resource- and energy-saving technologies, and the enhancement of operational and technological characteristics of the rectification plants are a prerequisite. A promising direction to solve this problem is to use a non-stationary (cyclic) mode of operation of the plants, based on the alternating change of the periods of the steaming periods and liquid overflow

Енергетична залежність промислово розвинутих країн вимагає альтернативних джерел енергії, одним з яких є етиловий спирт (біоетанол). Для забезпечення конкурентоспроможності біоетанолу над вуглеводними енергоносіями, необхідною умовою є розробка та впровадження інноваційних ресурсо- та енергозберігаючих технологій, підвищення експлуатаційно-технологічних характеристик ректифікаційних установок. Перспективним напрямком вирішення цієї проблеми є використання нестаціонарного (циклічного) режиму роботи установок, заснованого на поперемінній зміні періодів пропарювання та переливу рідини
Keywords: кафедра біотехнології продуктів бродіння і виноробства; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка; брагоректифікаційна установка; brewery rectification unit; розгінна колона; booster column; спирт; alcohol; пара; steam; спиртовмісні фракції; alcohol-containing fractions; домішки; impurities; циклічна ректифікація; cyclic rectification